Tablet Audiometry in Canada's North: A Portable and Efficient Method for Hearing Screening. (22nd July 2016) - Rourke, Ryan; Kong, David Chan Chun; Bromwich, Matthew
Abstract : Background: Access to hearing health care is limited in many parts of the world, creating a lack of prompt diagnosis, which further complicates treatment. The use of portable audiometry for hearing loss testing can improve access to diagnostics in marginalized populations. Our study objectives were twofold: (1) to determine the prevalence of hearing loss in children aged 4 to 11 years in Iqaluit, Nunavut, and (2) to test and demonstrate the use of our tablet audiometer as a portable hearing‐testing device in a remote location. Study Design: Prospective cross‐sectional observational. Setting: Remote elementary schools in 3 Canadian Northern communities. Subjects and Methods: Tablet audiometers were used to test hearing in 218 children. Air conduction pure tones thresholds were obtained at 500, 1000, 2000, and 4000 Hz. Children with hearing loss ≥30 dB in either ear were referred for audiology services. Results: Tablet audiometry screening testing revealed abnormal results in 14.8% of the study participants. No significant difference in the rate of hearing loss was seen by sex; however, the rate of hearing loss decreased significantly with increasing age. The median duration of the hearing test was 5 minutes 30 seconds. Conclusions: Of the study population, 14.8% tested positive for hearing loss based on our interactive tablet audiometer. In this setting, the tablet audiometer was both time efficient and largely language independent. This type of testing is valuable for providing much‐needed hearing health care for high‐risk populations in rural and remote areas where audiology services are often unavailable.